Penyebaran Dakwah Islam Populer di TV Indonesia Pasca Rezim Suharto - Qosim, Ahmad Afrizal (STAI Darul Kamal NW Kembang Kerang, 2023)
This dissertation examines the emergence of televised da'wah (Islamic propagation) following the downfall of the Suharto regime in Indonesia. The proliferation of da'wah programs on television, fueled by the country's Islamization and conservative Islamic influences, disrupted traditional authorities and reshaped religious dynamics. Through an ethnographic study of post-Suharto da'wah television ecology, Siddik highlights the role of charismatic religious preachers both on-screen and in real life, underscoring their influence in the contest for religious authority. The book presents historical evidence demonstrating the global trend of television preachers and sociological evidence illustrating how society supports da'wah programming, considering it a valuable medium for religious education. Overall, the dissertation asserts that the modern era's transformation of religious authority in Indonesia has been profoundly shaped by television, further solidifying the position of religious preachers in the religious domain struggle.